Safe Use of Replicating Bacteria in Biological Control - Jackson, T.A.; O’Callaghan, M.; Glare, T.R. (Phytoprotection, 1998)
Naturally occurring entomopathogenic bacteria provide an important resource for pest control. Greatest benefit will be obtained from the application of replicating bacteria which can establish in the host's environment and provide long term control. Bacteria developed for pest control are required to be safety tested and registered, yet bacteria are frequently introduced into the environment to enhance plant growth or aid soil processes without regulation. Why then, is the use of insect pathogenic bacteria treated differently? Augmentation of bacteria already present in the environment is unlikely to have any unwanted side effects as application is only changing the spatial and temporal distribution of the microbe and will have little long term effect on the total population. Users of the bacteria, however, will be exposed to the bacterium at a level higher than experienced naturally and potential adverse effects of this interaction should be addressed through Tier 1 safety testing. Non-target organisms should also be tested. If new organisms (exotic strains or modified bacteria) are to be introduced to the environment, their potential effects on the environment should be considered. The question of horizontal gene flow from applied bacteria also needs to be addressed. A better understanding of microbial ecology and Systems for tracking new strains and genes are essential to develop appropriate assessment procedures to ensure the safe utilisation of bacteria in biological control.